Genetic and biochemical characterizations of Zika virus NS2A protein - Xianwen Zhang; Xuping Xie; Jing Zou; Hongjie Xia; Chao Shan; Xinwen Chen; Pei-Yong Shi (Emerging Microbes and Infections)
Zika virus (ZIKV) can cause devastating congenital Zika syndromes in pregnant women and Guillain-Barre syndrome in adults. Understanding the molecular mechanism of ZIKV replication is essential for antiviral and vaccine development. Here we report the structural and functional characterization of ZIKV NS2A protein. Biochemical structural probing suggests that ZIKV NS2A has a single segment that traverses the ER membrane and six segments that peripherally associate with the ER membrane. Functional analysis has defined distinct NS2A residues essential for viral RNA synthesis or virion assembly. Only the virion assembly-defective mutants, but not the RNA synthesis-defective mutants, could be rescued through trans complementation with a wide-type NS2A protein. These results suggest that the NS2A molecules in virion assembly complex could be recruited in trans, whereas the NS2A molecules in viral replication complex must be recruited in cis. Together with previous results, we propose a flavivirus assembly model where NS2A plays a central role in modulating viral structural and nonstructural proteins as well as genomic RNA during virion assembly.